Intentional Occlusion of the Left Subclavian Artery in Diseases of the Thoracic Aorta - Cerezo, Marcelo Héctor (2011)
Bertoni and et al. (1) present an interesting experience in occlusion of the left subclavian artery (LSA) in order to improve the proximal fixation of tubular aortic endovascular devices to treat acute type B dissections (n = 4; 13.8%) or chronic (n = 14, 48.3%), intramural hematoma (n = 1; 3.4%), true aneurysm (n = 7; 24.1%), aortic ulcer (n = 1; 3.4% ) and traumatic pseudoaneurysm (n = 2; 6.8%). The percentage of occlusion of the subclavian artery in this series is similar to that observed in our series of patients. The work has a good statistical analysis and is supported by an extensive and important bibliography. It has been recently suggested that the use of self-expanding devices with proximal end point with free flow stent in the treatment of aortic dissections carries some risk of complications, such as retrograde dissection to the ascending aorta. This complication is the result of trauma which can lead that bare stent. (2, 3) The incidence of stroke may reach 7% (4, 5) according to what was observed in the EUROSTAR registry.